Suture‐Free Ureterovesical Anastomosis Using a Microvascular Anastomosis System: Canine Cadaveric Study. Issue 6 (5th May 2015) - Bertran, Judith; Wavreille, Vincent A.; Ham, Kathleen L.; McLoughlin, Mary A.; Adin, Christopher A.
<x xml:space="preserve">Abstract</x> Objective To describe a suture‐free ureterovesical anastomosis using a microvascular anastomotic system (MAS) and compare the surgical time and bursting pressure to a sutured ureterovesical anastomosis (SA) with and without an extravesical seromuscular tunnel (EVSMT). Study Design Randomized, unblocked design, ex vivo study. Animals Three canine cadavers. Methods For each cadaver, the ureters were sectioned into 3 equal lengths. The 6 sections were randomly assigned to receive either the MAS or end‐side SA. The first cadaver (3 MAS, 3 SA) was used to refine the technique, and the remaining 2 cadavers were used for evaluation. Surgical time and bursting pressure of the anastomosis were compared between MAS and SA (n = 6 per technique). After bursting pressure testing of each anastomosis, an SMT was created over the anastomoses. Bursting pressures were again recorded and compared across techniques. Results The surgery time was significantly shorter for MAS (median 5.4 minutes) than SA (median 15.8 minutes; P = .002). The bursting pressure was significantly higher for MAS (median 189.5 cmH2O) than SA (median 64 cmH2O; P = .002). The bursting pressure for MAS‐EVSMT (median 398.5 cmH2O) was not significantly different from the SA‐EVSMT (median 321 cmH2O, P = .567); however, the creation of an SMT significantly increased the bursting pressure for both techniques (P = .028, respectively). Conclusion This study demonstrated the feasibility of a suture‐free ureterovesical anastomosis in the canine cadaver using a commercially available MAS. The MAS anastomosis was faster and resulted in higher bursting pressures than SA. The creation of an SMT improved the bursting resistance of both techniques but there was no difference between the techniques covered by an EVSMT.